Histopathological Study of Some Organs After Long-Term Treatment With Dexamethasone in Male Rabbits. - Hussein, Adel J.; Majeed, Majdi F.; Abbas, Ali S. (Science Journal of University of Zakho, 2014)
The purpose of the study was to determined the histopathological changes in the adrenal gland, Kidney and liver which results from treatment with dexamethasone(DEX) .Thirty local male rabbits in Basra city were divided into three groups,the first group control group was given the normal saline orally , group two were orally given DEX. (0.2 mg/ k g/ BW) and the third group was treated with oral administration of DEX.at a dose of (1 mg. / k g/ BW) for (60) days. The results showed several histopathological changes in the adrenal gland of rabbits in both treated groups represented by congestion of blood vessels, degeneration, vaculation and necrosis of cells in the zona glomerulosa and zona fasciculata of the adrenal cortex. In treated rabbits,the histological section of kidney show some changes represented by degeneration, edema and cells necrosis of epithelial lining of convoluted tubules, infiltration of inflammatory cells and atrophy of some glomeruli. Liver of treated rabbits show ballooning hepatocytes and extension the sinuses.